The Influence of Brand Image, Price and Promotion on Purchasing Decisions of Aquviva Mineral Water Products among Makassar City - Andi Alfianto Anugrah Ilahi; Muhammad Syauqi Said (Jurnal Ilmiah Multidisiplin Amsir, 2026)
This study aims to analyze the influence of brand image, price, and promotion on purchasing decisions for Aquviva mineral water products among consumers in Makassar City. A quantitative research approach was employed, using structured questionnaires distributed to individuals who have purchased Aquviva mineral water. The sample size was determined using the Roscoe sampling technique. Data were analyzed through multiple linear regression with the support of SPSS version 27. The findings indicate that brand image and price do not have a significant effect on purchasing decisions, while promotion has a significant positive influence. Simultaneously, brand image, price, and promotion collectively contribute to explaining purchasing decisions. These results suggest that promotional activities play a crucial role in driving consumer purchasing behavior toward Aquviva mineral water in Makassar City.